Indonesia and Poland: language (foreign) policy as a soft power - Anna Grzywacz (UPT P2M Politeknik Negeri Malang, 2012)
Language policy is a major factor assisting a country foreign policy. Polish language policy seems to be less effective than Indonesian. However, both states have equally considerable potentials, but in the case of Poland, it seems that the significance of culture policy is not very much appreciated. Cultural policy, a primarily important element of creating country’s image in the world, strengthens the international position and seems to have ability to impact on the influences by the Western cultural domination. This article presents discussion on Polish and Indonesian language policy. Starting with general concepts of soft power and language policy, the writer presents general comparisons between Indonesian and Polish’s language policy. This article concludes that Indonesian language policy is somewhat better than Polish’s.